Economic valuation of protection and production forests in pekalongan regency. Issue 1 (March 2021) - Harini, R.; Yuniantari, R.; Ariani, R D
Abstract: Regional autonomy authorizes local governments to optimize sources of income, one of which is through natural resources. Pekalongan Regency is a district in Central Java which has the potential of forest resources covering an area of 28, 486 Ha including limited protected forests, production forests and limited production forests managed by Perum Perhutani. Forests are renewable natural resources that need to be managed sustainably to enable them to fulfill their (economic, social, environmental sustainability) functions according to sustainable development principles. Considering that at present some people do not have insights into the values of forest resources, especially their intangible benefits, this present study aimed to analyze the total economic value of protection and production forests to inform people about the economic value of forest resources. This study used a descriptive-quantitative method with primary and secondary data sources. The quantitative data processing technique used was the Total Economic Value model supported with the market price method, the travel cost method, and the benefit transfer method. The results of the analysis revealed that the economic value of protection and production forests in Pekalongan Regency is IDR. 232, 355, 092, 970. The indirect use value (41.36%) of the forests indicates that forests have substantial intangible benefits. The total economic value analysis of the forests can be used as a recommendation for local governments and stakeholders in allocating forest resources to keep them in the sustainable development order.